Flow field characteristics of a coherent jet using various lance tip structures - Guang-sheng WEI; Rong ZHU; Shu-jiang CHENG; Fu-hai LIU; Kai DONG; Liu-jie YAO (工程科学学报, 2020)
Coherent lances have been playing an extremely important role in the process of supplying oxygen to an electrical arc furnace, which has been widely used in metallurgy, and its metallurgical and operational benefits have been well reported. When compared with the conventional supersonic oxygen lance, the coherent lance could increase the oxygen utilization rate, strengthen penetration ability, and achieve a good stirring effect. However, there was limited research about the flow field characteristics of a coherent jet using different restriction structures for a coherent lance tip. This paper analyzed velocity and temperature profiles at various parameters and conditions. Both numerical simulation and combustion experiment have been carried out to investigate the velocity and temperature profiles using three kinds of restriction structures at room and high ambient temperature conditions. Further, the impact diameter and depth of the molten bath have also been analyzed at a certain lance height. The result shows that the restriction structure could delay energy transmission in a radial direction, which enlarges a high-temperature zone in an axial direction, resulting in the increase of the velocity potential core length and the improvement of the mixing ability of the main oxygen jet.